The Effect of Implementing Customer Relationship Management, Pipeline, and Campaigns on Company Operations - Beni Nurhalim; Rizal Ramdan Padmakusumah (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the effect of Customer Relationship Management (CRM), Pipeline, and Campaign implementation on Company Operations. The rapid development of technology and increasing business competition require companies to manage customer relationships, workflow processes, and campaign activities effectively in order to improve operational performance. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees directly involved in CRM, pipeline, and campaign activities. The sampling technique was determined using the Slovin formula based on the research population. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results indicate that Campaign and Pipeline have a positive and significant effect on Company Operations, while CRM does not have a significant direct effect on Company Operations. These findings suggest that operational effectiveness is more strongly influenced by the successful execution of campaigns and systematic workflow management than by CRM implementation, which has not yet been optimally integrated into operational processes. This study provides managerial implications, emphasizing the importance of strengthening data-driven campaign strategies, optimizing pipeline management, and enhancing CRM integration into operational processes to achieve sustainable operational performance improvement.